Histochemical studies on the testis of buffalo during prenatal life - KAUR, MANJINDER; BANSAL, NEELAM; UPPAL, VARINDER (The Indian Journal of Animal Sciences, 2011)
The present study was conducted on both the testes from 15 buffalo foetH to localize the distribution pattern of various histochemical moieties to correlate the functional activity. The PAS and ABIPAS reactions were stronger in the gemlinal epithelium, basement membrane and rete testis than the seminiferous tubules and tunica albuginea. The reaction of basic proteins was strong in the germinal epithelium, tunica vasculosa and rete testis than the basement membrane, seminiferous tubules and tunica fibrosa. The reaction of sudanophilic lipids was strong in tunica vasculosa and interstitium as compared to rete testis and seminiferous tubules of the fetal testes. The variation in the distribution of acid and neutral mucopolysaccharides, basic proteins and lipids in the testes of buffalo foetii may be due to the proliferation of various cell types and their steroidogenic activity at differentstages of testicular development. Â